KONDISI SOSIAL NELAYAN PASCA TIMBULNYA TAMBANG INKONVENSIONAL (TI) APUNG DI BANGKA BELITUNG - WAHYU ADI (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2012)
Islands Province of Bangka-Belitung as the largest tin producers in Indonesia, also has good potential for fisheries. Ocean territory which covers about 79.9% of land area, creating a potential fishing area to fishermen in this province. Act. 32 Year 2004 regarding Regional Autonomy and the Minister of Industry and Trade Decree No. 1999 Year 1999 which states categorized as tin-free goods, make a lot of social changes in society Bangka Belitung. Exploit tin, become a tempting option for the community. Fishermen, as a part of society, as actors fishing, faced with the choice to remain to be a fisherman or turned into tin floating-miners (TI Apung)